К проблеме территориальной организации государства Рюриковичей в Х – первой половине XI в. - Роменский, А.А. (Хазарский альманах, 2020)
The article deals with the problem of the territorial structure of the state of Rurikids in the 10th – the fi rst half of 11th century AD. The statehood of the Kievan princes in the 10th century AD seems to be a typical early medieval “barbaric” polity in which their real power did not extend beyond the fortifi ed protocity centers. The analysis of the sources (the Primary Chronicle, the treatises of Constantine Porphyrogenitus, the Jewish-Khazar documents, the “Bavarian Geographer”) allows us to identify most of the toponyms of various written traditions. Ethnic tribes of the Eastern Slavs had their own political elite. Their relations with the Rus’ were limited only to collecting tribute, “feeding” the prince and his retinue during visitation of the territories (“poliudie”), as well as participation in foreign policy military actions. Despite the differences between the ruling elite of Rus’ and the Slavs, there is a gradual incorporation of it in the 10th–11th centuries AD. The ethnic tribal groups of the Slavs do not disappear even in the fi rst half of the 11th century AD. The lists of sons of Prince Vladimir in the chronicle articles at 6496 (988) and 6488 (980) seems to be a textual insert. A possible source of it is the annalistic record. The views of researchers on administrative reform or political reorganization in Rus’ at the end of the 10th century do not fi nd any confi rmation. The changes in the system of corpus fratrum are established only after 1054 (the testament of Prince Yaroslav).